Features of auditing of labor law on agricultural enterprises - Yeltsova, J.; Musatova, Inna; Мусатова, Інна Миколаївна; Мусатова, Инна Николаевна (ТДАТУ, 2018)
In a market economy, the main factor in the sustainable development of society is the increase in the material interest of employees in improving the performance of activities on the basis of ensuring close interrelation of the size of the income of working with the quantity and quality of labor they spend. The payroll accounting system plays an important role. Creating an effective system and methods for accounting for payroll calculations is a major task. Audit of payroll calculations at agricultural enterprises, as a rule, takes the bulk of the audit, as this accounting area is rather specific and requires the attention of auditors and concentration.
Keywords: agricultural enterprises; income tax of individuals; audit risk; wages